Neutrophil Extracellular Trap Formation and Syndecan-1 Shedding Are Increased After Trauma. Issue 3 (September 2021) - Goswami, Julie; MacArthur, Taleen; Bailey, Kent; Spears, Grant; Kozar, Rosemary A.; Auton, Matthew; Dong, Jing-Fei; Key, Nigel S.; Heller, Stephanie; Loomis, Erica; Hall, Nathan W.; Johnstone, Andrea L.; et al.
ABSTRACT: Background: Damage-associated molecular patterns (DAMPs) stimulate endothelial syndecan-1 shedding and neutrophil extracellular traps (NET) formation. The role of NETs in trauma and trauma-induced hypercoagulability is unknown. We hypothesized that trauma patients with accelerated thrombin generation would have increased NETosis and syndecan-1 levels. Methods: In this pilot study, we analyzed 50 citrated plasma samples from 30 trauma patients at 0 h (n = 22) and 6 h (n = 28) from time of injury (TOI) and 21 samples from healthy volunteers, for a total of 71 samples included in analysis. Thrombin generation was quantified using calibrated automated thrombogram (CAT) and reported as lag time (LT), peak height (PH), and time to peak (ttPeak). Nucleosome calibrated (H3NUC) and free histone standardized (H3Free) ELISAs were used to quantify NETs. Syndecan-1 levels were quantified by ELISA. Results are presented as median [interquartile range] and Spearman rank correlations. Results: Plasma levels of H3NUC were increased in trauma patients as compared with healthy volunteers both at 0 h (89.8 ng/mL [35.4, 180.3]; 18.1 ng/mL [7.8, 37.4], P = 0.002) and at 6 h (86.5 ng/mL [19.2, 612.6]; 18.1 ng/mL [7.8, 37.4], P = 0.003) from TOI. H3Free levels were increased in trauma patients at 0 h (5.74 ng/mL [3.19, 8.76]; 1.61 ng/mL [0.66, 3.50], P = 0.002) and 6 h (5.52 ng/mL [1.46, 11.37]; 1.61 ng/mL [0.66, 3.50], P = 0.006). Syndecan-1 levels were greater in trauma patients (4.53 ng/mL [3.28, 6.28]; 2.40 ng/mL [1.66, 3.20], P < 0.001) only at 6 h from TOI. H3Free and syndecan-1 levels positively correlated both at 0 h (0.376, P = 0.013) and 6 h (0.583, P < 0.001) from TOI. H3NUC levels and syndecan-1 levels were positively correlated at 6 h from TOI (0.293, P = 0.041). TtPeak correlated inversely to H3 NUC (−0.358, P = 0.012) and syndecan-1 levels (−0.298, P = 0.038) at 6 h from TOI. Conclusions: Our pilot study demonstrates that trauma patients have increased NETosis, measured by H3NUC and H3Free levels, increased syndecan-1 shedding, and accelerated thrombin generation kinetics early after injury.